What are individual‐level nature amends? Rescaling biodiversity offsetting from the community members' perspective - Tupala, Anna‐Kaisa; Huttunen, Suvi; Aro, Riikka; Lizarazo, Clara; Tuittila, Satu (John Wiley & Sons, 2024)
Effective solutions to biodiversity loss are multidimensional, requiring engagement from diverse stakeholders across various sectors and commitment levels. In this context, voluntary actions from community members emerge as a valuable addition to the large-scale nature conservation activities conducted by states and municipalities. Such actions complement biodiversity protection measures and legal requirements aimed at companies. This article delves into the rescaling of biodiversity offsetting to the community members level and explores it from the perspective of community members. Through workshops organized in four Finnish municipalities, participants were prompted to reflect on biodiversity offsetting in their daily lives. The results show community members' limited resources to conduct pro-biodiversity actions and highlight their diverse interpretations of the topic. Beyond direct biodiversity-enhancing action, like maintaining rural biotopes, eradicating alien species, or protecting forests, workshop participants called for indirect actions. These included education, eco-taxes, and the development of sharing economies. Thus, rather than solely focusing on biodiversity offsetting or the mitigation hierarchy, these suggestions underscore the need for diverse pro-biodiversity actions at the community member's level. Furthermore, the results highlight the need for support that enables community members and communities' work for biodiversity. Introducing the concept of nature amends addresses this need, enhancing the mitigation hierarchy's capacity to incorporate community members in nature conservation endeavors.
Keywords: biodiversiteetti; luonnonsuojelu; luonnon monimuotoisuus; kestävä kehitys; ekologinen kompensaatio; kansainvälinen yhteistyö; paikallisyhteisöt